2013
DOI: 10.1074/jbc.c113.503094
|View full text |Cite
|
Sign up to set email alerts
|

Differential Utilization of TATA Box-binding Protein (TBP) and TBP-related Factor 1 (TRF1) at Different Classes of RNA Polymerase III Promoters

Abstract: Background: TATA box-binding protein-related factor 1 (TRF1) was believed to be required for all RNA polymerase III transcription in Drosophila. Results: Chromatin immunoprecipitations and transcription assays indicate TATA box-binding protein (TBP) is utilized at U6 snRNA promoters. Conclusion: Although TRF1 is required for tRNA transcription, TBP is used for U6 transcription. Significance: Different classes of RNA polymerase III promoters differentially utilize TBP and TRF1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Recent work in our lab confirmed that TRF1 replaced TBP as a subunit of TFIIIB for tRNA gene transcription in fruit flies. Interestingly, however, we also found that transcription of U6 snRNA genes by Pol III instead utilized TBP rather than TRF1 . Thus, different types of Pol III promoters in insects can differentially utilize either TBP (at Type III promoters) or TRF1 (at Type I and Type II promoters) as a component of TFIIIB.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Recent work in our lab confirmed that TRF1 replaced TBP as a subunit of TFIIIB for tRNA gene transcription in fruit flies. Interestingly, however, we also found that transcription of U6 snRNA genes by Pol III instead utilized TBP rather than TRF1 . Thus, different types of Pol III promoters in insects can differentially utilize either TBP (at Type III promoters) or TRF1 (at Type I and Type II promoters) as a component of TFIIIB.…”
mentioning
confidence: 70%
“…The TFIIIB subunits were overexpressed or co‐overexpressed in stably transfected S2 cells under the control of the copper‐inducible metallothionein promoter as previously described . Proteins were partially purified or copurified by nickel chelate affinity chromatography also as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…It can bind to the TATA box along with TFIIA and TFIIB and substitute for TBP in the transcription of some Pol II promoters in vitro (Hansen et al 1997;Holmes and Tjian 2000). Moreover, TRF1 associates with BRF1 (an RNA Pol III transcription factor) and mediates tRNA gene transcription from Pol III promoters (Takada et al 2000;Isogai et al 2007a;Verma et al 2013). Thus, TRF1 participates in both Pol II and Pol III transcription.…”
Section: Trf1mentioning
confidence: 99%
“…Likewise, the transcription initiation factors for Pol I and Pol III (SL1/Tif-1B and TFIIIB, respectively) contain a TFIIB-related protein and TBP (or a TBP-related protein (Trf1) in Drosophila) counterparts (7)(8)(9)20).…”
mentioning
confidence: 99%